Facebook likes: a study of liking practices for humanitarian causes. (1st January 2014) - Brandtzaeg, Petter Bae; Haugstveit, Ida Maria
Civic engagement on Facebook has evolved, but there are still few studies of people's motivations and reasons for liking humanitarian causes on Facebook. Introduced in 2009, the 'like' button has become a part of users' daily Facebook routines and a way for them to engage in humanitarian causes. Content analysis from a survey ( N = 405) revealed six different liking practices for humanitarian causes on Facebook: 1) socially responsible liking; 2) emotional liking; 3) informational liking; 4) social performative liking; 5) low-cost liking; 6) routine liking. Interestingly, informational-driven liking was much less common than the more socially and emotionally motivated reasons for liking. The majority of the respondents also believe such likes help in promoting humanitarian causes; only a few had unliked such causes. The implications of these findings for understanding the nature and function of Facebook likes as a new form of civic engagement and humanitarian support are discussed.